2015
DOI: 10.1007/s00468-015-1261-9
|View full text |Cite
|
Sign up to set email alerts
|

Pine mortality in southeast Spain after an extreme dry and warm year: interactions among drought stress, carbohydrates and bark beetle attack

Abstract: Key message Pine mortality was related to water stress, which caused xylem cavitation.Hydraulic failure and carbon starvation are likely interrelated, and bark beetles attacks did not seem to be directly involved. Abstract Forests are extremely important for society given the many services they provide. Climate models reflect increases in temperature and less annual rainfall, which will generate hotter drier environments. Under these conditions, it is predicted that forest ecosystems will be severely affected,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 38 publications
3
44
0
2
Order By: Relevance
“…This loss of resilience may reflect the poor vigor of these trees, which responded to recurrent droughts by showing a reduction in growth rates and by needle shedding. These symptoms may portend widespread tree mortality, as has been observed in other drought-prone pine plantations [10]. Therefore, our results confirm an increased sensitivity of planted P. pinaster stands to drought which suggests that they will become increasingly vulnerable to drought-triggered tree mortality in the coming decades [17].…”
Section: Discussionsupporting
confidence: 76%
“…This loss of resilience may reflect the poor vigor of these trees, which responded to recurrent droughts by showing a reduction in growth rates and by needle shedding. These symptoms may portend widespread tree mortality, as has been observed in other drought-prone pine plantations [10]. Therefore, our results confirm an increased sensitivity of planted P. pinaster stands to drought which suggests that they will become increasingly vulnerable to drought-triggered tree mortality in the coming decades [17].…”
Section: Discussionsupporting
confidence: 76%
“…Indeed, previous findings suggested that warming superimposed on drought is going to exacerbate the drought stress experienced by trees and could lead to more frequent drought‐associated mortality events (Williams et al ; Allen et al ; García de la Serrana et al ). However, after a period of five years under warmer (+ ≈ 5 °C) and drier (−50% precipitation) conditions, we observed no mortality or significant decline at our study site.…”
Section: Discussionmentioning
confidence: 99%
“…It is the prevailing tree in dry and semiarid areas and broadly used in reforestation and restoration activities (Pausas et al, 2004) because of its high rates of seedling survival and growth (Barberá, Martínez-Fernández, Álvarez-Rogel, Albaladejo, & Castillo, 2005;Fuentes, Valdecantos, Cortina, & Vallejo, 2007) and its plasticity to changes in the soil environment (Broncano, Riba, & Retana, 1998). Nevertheless, its use in high water-stressed semiarid systems may be detrimental to stimulate successional processes (Bellot, Maestre, Chirino, Hernández, & De Urbina, 2004), and their adaptation may not be sufficient for future climatic scenarios (García de la Serrana, Vilagrosa, & Alloza, 2015).…”
Section: Pinus Halepensismentioning
confidence: 99%